2003
DOI: 10.1186/1471-2164-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, genomic characterization and over-expression of a novel gene, XRRA1, identified from human colorectal cancer cell HCT116Clone2_XRR and macaque testis

Abstract: Background: As part of our investigation into the genetic basis of tumor cell radioresponse, we have isolated several clones with a wide range of responses to X-radiation (XR) from an unirradiated human colorectal tumor cell line, HCT116. Using human cDNA microarrays, we recently identified a novel gene that was down-regulated by two-fold in an XR-resistant cell clone, HCT116 Clone2_XRR . We have named this gene as X-ray radiation resistance associated 1 (XRRA1) (GenBank BK000541). Here, we present the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Up-regulated expression of XRRA1 has been linked to reduced capacity for DNA damage repair in human cell lines. 36 Overall, Gene Ontology classification based on the molecular function of these 2629 genes indicated that the set was enriched for oxidoreductase and dehydrogenase activity but also for KRAB domain containing zinc finger transcription factors (Table 1). The data were very similar when 1-mb windows were used instead.…”
Section: Resultsmentioning
confidence: 99%
“…Up-regulated expression of XRRA1 has been linked to reduced capacity for DNA damage repair in human cell lines. 36 Overall, Gene Ontology classification based on the molecular function of these 2629 genes indicated that the set was enriched for oxidoreductase and dehydrogenase activity but also for KRAB domain containing zinc finger transcription factors (Table 1). The data were very similar when 1-mb windows were used instead.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely known that cycle arrest results in the inhibition of cell proliferation. Cyclin D1 and cyclin A are regulated by p21 to influence the cell cycle and cell proliferation [ 1 , 3 ]. Overexpression of cyclin A and cyclin E could induce G 1 arrest [ 4 ], whereas p21 mediated G2-phase cell cycle arrest [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Human XRRA1 cDNA is 1987 nt long and encodes a protein of 559 aa. Mesak et al [ 1 ] detected XRRA1 expression in normal tissues/organs and cells, as well as in various cancer cell types (such as breast cancer, glioma, melanoma, lung cancer, and neuroblastoma) by RT-PCR and found that XRRA1 was present in all cell types, although the expression level was variable. To understand further the possible function of the XRRA1 gene, we overexpressed XRRA1 in six different tumor cell lines and found significantly increased cell proliferation compared with the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIR4696 encodes a microRNA, which are involved in post-translational gene expression regulation 51 . The XRRA1 gene product is believed to regulate cell response to X-radiation exposure; the lead SNP in the EA group analysis falls within the XRRA1 gene 52 . SPCS2 encodes a subunit of the microsomal signal peptidase complex, which removes signaling peptides from newly-formed proteins as they move to the endoplasmic reticulum 53 .…”
Section: Resultsmentioning
confidence: 99%